Emulsion Properties of Poly(n-butyl acrylate)/Poly(methyl methacrylate) Polymer with Core-Shell Structure - Zhu, Guo-Quan; Wang, Fa-Gang; Xu, Ke-Jing; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
Poly(n-butyl acrylate)/poly(methyl methacrylate) core-shell structure polymer emulsion was synthesized by two-stage emulsion polymerization with sodium dodecyl sulfonate and polyoxyethylene nonylphenol ether (OP-10) as composite emulsifier, distilled water as the continuous medium and potassium persulfate as the initiator. Differential scanning calorimetry and dynamic light scattering were used to investigate the compatibility of two polymers and the size of Poly(n-butyl acrylate)/poly(methyl methacrylate) core-shell polymer particles, respectively.